Development of a test method for evaluating the crushing behaviour of unidirectional laminates. (December 2017) - Bru, Thomas; Waldenström, Paul; Gutkin, Renaud; Olsson, Robin; Vyas, Gaurav M
More fundamental test methods are needed to assist the development of physically based and truly predictive simulation tools for composite materials under crash conditions. In this paper, a unidirectional flat specimen that can be used to validate the predicted behaviour from a simulation to the physical behaviour in the experiment is developed. A systematic experimental investigation is conducted to evaluate the influence of the trigger geometry on the crushing response by selecting two trigger types and different trigger angles. For longitudinal crushing, the traditional bevel trigger leads to out-of-plane failure by splaying with a limited amount of in-plane fracture, while the proposed trigger achieves a high amount of compressive fragmentation failure. For transverse crushing, the symmetry of the proposed new trigger improves the specimen stability during the crushing process. It is also observed that the weft threads of the unidirectional fabric reinforcement used for the tests have a strong influence on the longitudinal crushing response. The boundary conditions of the test and the information on the specimen failure gleaned from video recordings and microscopic inspections are discussed in order to facilitate a future correlation with modelling results.